2021
DOI: 10.2807/1560-7917.es.2021.26.1.2001365
|View full text |Cite
|
Sign up to set email alerts
|

Control of a COVID-19 outbreak in a nursing home by general screening and cohort isolation in Germany, March to May 2020

Abstract: Elderly care facilities have become a major focus of coronavirus disease (COVID-19) control. Here, we describe an outbreak of COVID-19 in a nursing home in Germany from 8 March to 4 May 2020 (58 days), and the effect of an intervention of general screening and cohort isolation. COVID-19 cases among residents and staff were recorded on a daily basis from the first positive SARS-CoV-2 test from a resident on 8 March 2020, until 4 May 2020 when the last staff member was classified COVID-19 negative. Eighty of 160… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 15 publications
(38 reference statements)
0
21
0
Order By: Relevance
“…In contrast, viral load at the beginning of a SARS-CoV-2 infection is low, and rapidly increases after the test is performed. Unless these individuals are identified by a parallel RT-qPCR, a false negative RDT may cause and fuel outbreaks [23] . Additionally, incorrect swabbing may strongly decrease in-vitro viral load in the sample and falsely suggest a lower viral load according to a preprint analysis [24] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, viral load at the beginning of a SARS-CoV-2 infection is low, and rapidly increases after the test is performed. Unless these individuals are identified by a parallel RT-qPCR, a false negative RDT may cause and fuel outbreaks [23] . Additionally, incorrect swabbing may strongly decrease in-vitro viral load in the sample and falsely suggest a lower viral load according to a preprint analysis [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Given the variable time latencies between testing and results [24], and the need to repeat testing in many instances, isolation and cohorting strategies were implemented in nursing homes to divide the residents into defined groups based on COVID-19 status. Many studies reported the common practice of cohorting positive cases within a separate COVID-19 unit [47][48][49]. It was recommended that specific staff members be allocated to these units to reduce dissemination and allow for more focused care [50].…”
Section: Isolation and Cohortingmentioning
confidence: 99%
“…Following duplicate removal, title and abstract screening, and full-text screening, 61 met all inclusion criteria and were included in the review (Figure 1). Included studies (k = 61) varied in study design, comprising 6 cross-sectional studies [21][22][23][24][25][26], 7 case-control series [27,28], 22 prospective cohort studies , 1 longitudinal cohort study [51], 7 retrospective cohort studies [52][53][54][55][56][57][58], 7 prospective observational studies (i.e., observing the number of new cases in a facility after the implementation of IPC measures) [59][60][61][62][63][64][65], 1 retrospective observational study [66], 3 outbreak investigation reports [67][68][69], 1 post hoc analysis [70], 1 sequential follow-up study [71], 1 short-term prospective survey [72], 2 surveillance studies [73,74], and 7 mathematical modelling studies [75][76][77][78][79][80][81]. All studies were conducted before COVID-19 vaccinations became available in December 2020.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Fifteen studies were performed in the United States (USA) [28,36,38,41,45,49,51,52,55,69,72,[78][79][80][81]. Other included studies were performed in India [32], France [72], Canada [29,63], Italy [22,42,44,57,60,62,74], the United King-dom (UK) [35,40,50,53,58,65,75,76], Belgium [21,39], Korea [30,31,54,56], Taiwan [73], Germany [33,37,59,67,68,71] China [48], Finland [25], Spain [26], Japan …”
Section: Study Characteristicsmentioning
confidence: 99%